2001
DOI: 10.1287/isre.12.3.240.9709
|View full text |Cite
|
Sign up to set email alerts
|

Combining IS Research Methods: Towards a Pluralist Methodology

Abstract: T his paper puts forward arguments in favor of a pluralist approach to IS research. Rather than advocating a single paradigm, be it interpretive or positivist, or even a plurality of paradigms within the discipline as a whole, it suggests that research results will be richer and more reliable if different research methods, preferably from different (existing) paradigms, are routinely combined together. The paper is organized into three sections after the Introduction. In §2, the main arguments for the desirabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
544
0
38

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 791 publications
(592 citation statements)
references
References 68 publications
10
544
0
38
Order By: Relevance
“…Moreover, Petter and Gallivan [37] found that this combination is frequently used in IS studies involving MMR. Finally, the use of MMR responds to several calls to go beyond the dominance of positivist, quantitative research, [37], [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Petter and Gallivan [37] found that this combination is frequently used in IS studies involving MMR. Finally, the use of MMR responds to several calls to go beyond the dominance of positivist, quantitative research, [37], [51].…”
Section: Discussionmentioning
confidence: 99%
“…funds, researchers, web designers) is necessary. Finally, following Mingers, we are conscious of the limitations of the MMR, regarding philosophical, cultural, psychological and practical feasibility [51], however, despite the large amount of required resources, we are confident, based on the currently on-going data collection and data analysis, that those limitations are not insurmountable. Even though this paper contributes to the literature by providing two frameworks, one to analyse IT entrepreneur's turnover and the other to conduct a mixed methods research combining exploratory and triangulation design, future research will seek to apply and test those frameworks and generate interesting findings.…”
Section: Practical Implications Limitations and Future Researchmentioning
confidence: 99%
“…According to Kaplan and Duchon [45] and Mingers [46], [47], there is limited research that has employed methodological pluralism in the IS literature. Venkatesh et al, [48] mentioned that the use of mixed method approach (ie.…”
Section: Methodsmentioning
confidence: 99%
“…Combining these two data sources provided a broader set of data from a larger sample size, which increases the analysis possibilities, especially in relation to be able to do statistical tests (e.g., [32,33]). Using two methods for measuring the priorities and identifying dependencies also alleviated the risk for measurement bias as data can be analyzed across methods [34]. A major challenge in the creation of the survey and workshop instruments (selfcompletion questionnaires) was the choice of prioritization techniques.…”
Section: 2mentioning
confidence: 99%